DETEKSI DISTRIBUSI WHITE SPOT SYNDROME VIRUS PADA BERBAGAI ORGAN UDANG VANAME (Litopenaeus vannamei) - Hidayani, A.Aliah; Malina, Asmi C.; Tampangallo, Bunga R.; Fathurrahman, Achmad F. (Torani Journal of Fisheries and Marine Science, 2016)
One way to detect the presence of the White Spot Syndrome Virus in several organs Vaname shrimp (Litopenaeus vannamei) were infected with the method of Polymerase Chain Reaction (PCR). WSSV virus is known to attack various target organs, but it is difficult to detect early on shrimp. Therefore, this study aims to detect the presence of the distribution of White Spot Syndrome Virus in several organs Vaname shrimp (Litopenaeus vannamei) were infected with the Polymerase Chain Reaction method in order to early detection efforts for the prevention and treatment of diseases caused by the virus. Organ observed that the swimming legs, gills, stomach and antennal gland. Research stages include sample preparation and DNA extraction, DNA amplification and electrophoresis. DNA extraction was performed using the method DTAB and CTAB-DNA amplification is done by using nested PCR. The emergence of DNA bands is an indicator of the presence of WSSV in shrimp Vaname several organs which are then presented desktriptif. The results showed four WSSV infected organs were observed. Based on the appearance, the entire sample of the swimming leg and antennal gland positively infected, then successively gills and stomach. The swimming leg can be used to diagnose the disease early on shrimp WSSV Vaname without turning off the shrimp. Keywords : Distribution, Vanname shrimp, WSSV, PCR